2004
DOI: 10.1021/jp0365615
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Selectivity, and Solvation of a Model Chiral Stationary Phase

Abstract: The presence of chirality at an interface enables a surface to distinguish between enantiomers. The mechanism by which this selectivity occurs is complicated by the surface morphology, the possible involvement of the solvent, and the characteristics of the chiral molecules at the surface. In this article, atomic force microscopy (AFM), chemical force titrations, density functional theory, and molecular dynamics simulations are employed to examine surfaces terminated by (S)-and (R)-N-(1-phenylethyl)-N′-[3-(trie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 46 publications
(58 reference statements)
1
26
0
Order By: Relevance
“…Because of this, understanding the mechanism by which the mixture of solvents interacts with the solid stationary phase is of critical importance. The reagent of interest in this article is ( S / R )- N -(1-phenylethyl)- N ‘-[3-(triethoxysilyl)propyl]-urea or PEPU . PEPU may be readily covalently bonded to silica particles through a hydrolysis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, understanding the mechanism by which the mixture of solvents interacts with the solid stationary phase is of critical importance. The reagent of interest in this article is ( S / R )- N -(1-phenylethyl)- N ‘-[3-(triethoxysilyl)propyl]-urea or PEPU . PEPU may be readily covalently bonded to silica particles through a hydrolysis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…2 might have on the partitioning behavior of the protein between solid and liquid phases. Many groups, including our own [40,41], have found that the adhesion forces between the same pair of functional groups can be strongly affected by media of differing polarity, such as the methanol-water mixtures used here. Previous chemical force spectrometric measurements on methyl-and perfluoro-terminated SAMs [42] have shown results similar to those that we see here -the adhesive interactions become smaller by orders of magnitude when the polarity of the solution is decreased.…”
Section: Discussionmentioning
confidence: 97%
“…These methods and results for achiral separations, with respect to grafting densities, chain alignment, solvent density profiles near the substrate and interface regions, are enlightening also with respect to enantiomeric separations, for example, their simulations in which a chiral selector is covalently tethered to a planar slit pore solid support consisting of tertramethylsilane end caps, with no silanols on the surface. 12 Cann et al have carried out MD simulations of solvent effects on covalently-bonded selectors, in particular PEPU (N-(1-phenylethyl)-N 0 -3-(triethoxysilyl)propyl-urea), 52,53 DNB-leucine ((R)-N-(3,5-dinitrobenzoyl) leucine), DNB-phenyl glycine ((R)-N-(3,5-dinitrobenzoyl)phenylglycine) for solvents of variable composition, 35 proline-based selectors with variable numbers of proline moieties in the same mixed solvents, 40,42 1-(3,5-dinitrobenzamido)-1,2,3,4-tetrahydrophenanthrene or Whelk-O1 in n-hexane/2-propanol, water/methanol, and a supercritical solvent of CO2 and methanol. 36 Their studies describe the detailed nature of the interface for these types of selectors in the solvent systems.…”
Section: Preparing the Interface Solvent Effects On Covalently-bonded Selectorsmentioning
confidence: 99%
“…Cann et al have carried out MD simulations of solvent effects on covalently‐bonded selectors, in particular PEPU ( N ‐(1‐phenylethyl)‐ N ′‐ 3‐(triethoxysilyl)propyl‐urea), 52,53 DNB‐leucine ((R)‐ N ‐(3,5‐dinitrobenzoyl)leucine), DNB‐phenyl glycine ((R)‐ N ‐(3,5‐dinitrobenzoyl)phenylglycine) for solvents of variable composition, 35 proline‐based selectors with variable numbers of proline moieties in the same mixed solvents, 40,42 1‐(3,5‐dinitrobenzamido)‐1,2,3,4‐tetrahydrophenanthrene or Whelk‐O1 in n ‐hexane/2‐propanol, water/methanol, and a supercritical solvent of CO2 and methanol 36 . Their studies describe the detailed nature of the interface for these types of selectors in the solvent systems.…”
Section: Studies On Covalently Bonded Selectorsmentioning
confidence: 99%